Surface modification of polysquaraines to sense humidity within a second for breath monitoring - Zhou, Jin; Xiao, Xin; Cheng, Xue-Feng; Gao, Bi-Jun; He, Jing-Hui; Xu, Qing-Feng; Li, Hua; Li, Na-Jun; Chen, Dong-Yun; Lu, Jian-Mei (Sensors and actuators. B, Chemical, 2018)
•A novel humidity sensor based on polysquraine microspheres doped by gold nanoparticles has been prepared.•The optimized humidity sensor is of a response/recovery time as short as 1/4 s, a hysteresis less than 5% and impedance variation >105.•A prototype portable machine are manufactured to demonstrate its applicablity in real-time breath monitoring. Various conjugated polymer materials have been successfully applied in humidity sensors, but their response/recovery time are not satisfactory for breath humidity monitoring. In this research, a rapid and stable humidity sensor was fabricated from a polysquaraine, poly(1-phenylpyrrole-2-ylsquaraine) (PPPS) sample decorated by Au nanoparticles. Uniform PPPS microspheres in diameter were synthesized and loaded by gold nanoparticles (30 nm in diameter), and the structure was confirmed by X-ray photoelectron spectra and elemental mapping. Relative humidity (RH) values within the range of 11–95% were determined by testing the impedance response of the sensor at room temperature. The PPPS-2 sensor loaded with Au nanoparticles with 10% weight ratio to squaric acid offered the best humidity-sensing performance: the working range spreads from 11% to 95% RH; the response/recovery time is <1/4 s; its impedance variation reaches five orders of magnitude; the maximum hysteresis is 5%. Such a performance is attributed to electrical loading by gold and hydronium transportation. A portable device was fabricated for remote monitoring of breath humidity. Our results demonstrated that surface-engineered polysquaraines are of practical application in humidity measurement, and in particular, in breathing humidity monitoring.